2020
DOI: 10.1021/acsnano.0c02072
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of One-Dimensional Peierls-type Charge Density Wave in Twin Boundaries of Monolayer MoTe2

Abstract: One-dimensional (1D) metallic mirror-twin boundaries (MTBs) in monolayer transition metal dichalcogenides (TMDCs) exhibit a periodic charge modulation and provide an ideal platform for exploring collective electron behavior in the confined system. The underlying mechanism of the charge modulation and how the electrons travel in 1D structures remain controversial. Here, for the first time, we observed atomic-scale structures of the charge distribution within one period in MTB of monolayer MoTe2 by using scannin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…For the MTBs in ML MoSe 2 , TLL was also suggested by a photoemission spectroscopy experiment, whereas a low-temperature scanning tunneling microscopy and spectroscopy (LT-STM/S) study pointed to the Peierls-type CDW . A similar CDW has been suggested in the MTBs formed in MoTe 2 . On the other hand, Liu et al reported quantum well states (QWS) in finite length MTBs .…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…For the MTBs in ML MoSe 2 , TLL was also suggested by a photoemission spectroscopy experiment, whereas a low-temperature scanning tunneling microscopy and spectroscopy (LT-STM/S) study pointed to the Peierls-type CDW . A similar CDW has been suggested in the MTBs formed in MoTe 2 . On the other hand, Liu et al reported quantum well states (QWS) in finite length MTBs .…”
mentioning
confidence: 81%
“…2 A similar CDW has been suggested in the MTBs formed in MoTe 2 . 32 On the other hand, Liu et al reported quantum well states (QWS) in finite length MTBs. 1 Jolie et al provided experimental evidence of spin-charge separation and thus the TLL in the so-called 4|4E type MTB in MoS 2 .…”
mentioning
confidence: 99%
“…The CDW order could be excluded in our case as the STS data in Fig. 3c exhibit continuous suppression towards E F without any signature of CDW gap formation, in contrast to the well-defined gap structure in the STS spectra of other typical Q1D CDW systems 26,27 . On the other hand, the CDW fluctuations could cause a pseudogap opening, which may explain the spectral weight suppression 28,29 .…”
Section: Tll Origin Of the Spectral Weight Suppressionmentioning
confidence: 86%
“…17 As an alternative, molecular beam epitaxy (MBE) has been used to grow 2H-MoTe 2 thin films on graphene on 6H-SiC(0001), 18 SiO 2 , 19 GaAs(111)B, 20 CaF 2 , 21 InAs(111)/Si(111) 22 and c-Al 2 O 3 (0001), 23 although the small grain size of the grown layer results in poor transport properties. 23 Besides, the formation of a single MoTe 2 layer with different stoichiometry and diverse physical properties has been reported on highly oriented pyrolytic graphite (HOPG), [24][25][26] bilayer of graphene on SiC (BLG/SiC) 26,27 and MoS 2 . 28 However, the production of large domains of metallic 1T′ phase or the control of the fabrication of heterophase structures are still challenging, as a result of both the tendency of Te to desorb from the surface during the growth process and the small energy difference between the 1H and the 1T′ phases.…”
Section: Introductionmentioning
confidence: 99%